Defect Engineering in Carbon‐Based Electrocatalysts: Insight into Intrinsic Carbon Defects. (3rd April 2020) - Zhu, Jiawei; Mu, Shichun
Abstract: Functionalized carbon nanomaterials, as significant options for renewable energy systems, are widely utilized in diversified electrochemical reactions in virtue of property advantages. The inevitable defect sites in architectures greatly affect physicochemical properties of carbon nanomaterials, thus defect engineering has recently become a vital research orientation of carbon‐based electrocatalysts. The intentionally introduced intrinsic carbon defect sites in the frameworks can directly serve as the potential active sites owing to the altered surface charge state, modulated adsorption free energy of key intermediates, as well as diminished bandgap. Furthermore, the synergistic sites between intrinsic defects and heteroatom dopants/captured atomic metal species can further optimize the electronic structure and adsorption/desorption behavior, making carbon‐based catalysts comparable to commercial precious metal catalysts in electrocatalysis. With pressing research demands, the common configurations, construction strategies, structure–activity relationships, and characterization methods for intrinsic carbon defect‐involved catalytic centers are systematically summarized. Such theoretical and experimental evidences of intrinsic defect‐induced activity can reveal the active centers and relevant catalytic mechanism, thereby providing necessary guidance for the design and construction of highly efficient carbon‐based electrocatalysts and promoting their commercial applications. Abstract : Defect engineering can effectively improve the electrocatalytic activity of carbon‐based nanomaterials. This review summarizes the recent progress and discusses the structure–activity relationship of various defect sites comprising intrinsic carbon defects and their synergistic sites with extrinsic defects, in an attempt to provide insights into the development of rational construction and characterization means, as well as the in‐depth understanding of defect catalytic mechanism.